Method for producing die for extruding aluminum profiles, extrusion die, method for producing extrusion die blank material, and extrusion die blank material
By mixing steel powder with carbide, oxide and nitride powder and performing SPS sintering, combined with CVD coating layer treatment, the problem of insufficient hardness and wear resistance of aluminum extrusion mold material is solved, and the mechanical properties of the mold are significantly improved and lifespan.
Patent Information
- Application Number
- CN202380041071.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-19
- Filing Date
- 2023-05-19
- Publication Date
- 2024-12-27
AI Technical Summary
In the existing aluminum extrusion mold manufacturing methods, the hardness, tempering resistance and adhesion properties of the mold material are insufficient, which affects the life and performance of the mold.
Steel powder is mixed with a powder of carbide, oxide and nitride, and after discharge plasma sintering (SPS), the machined and chemical vapor deposition (CVD) coating layer are processed to form a high hardness and wear resistance. mold.
Significantly improves the mechanical and tribological characteristics of the mold, enhances hardness/toughness balance and tempering resistance, extends mold life, and reduces equipment use and steps during the manufacturing process.
Smart Images

Figure CN119212813A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a die for extruding an aluminum profile. The present invention also relates to a die for extruding an aluminum profile. In addition, the present invention relates to a method for producing a die blank material for preparing a die for extruding an aluminum profile, and such a die blank material. Background Art
[0002] The present invention relates to a method for producing a die for the extrusion of aluminum or its alloys. With the aid of extrusion, a preheated material is pushed through an extrusion die to produce a solid or hollow object of the desired cross-sectional profile. Extrusion allows the manufacture of complex cross-sections and a finished part with excellent surface finish can be obtained. In some cases, the desired cross-sectional shape of the extruded object may be very complex, which places high demands on the extrusion die. In the extrusion of aluminum, there are several factors that affect the die life and performance.
[0003] The conventional manufacturing method of the extrusion die includes a high isostatic pressing (HIP) step, a hot rolling step and a cut-to-length step. Patent EP1920079 discloses an example of steel for extrusion dies.
[0004] Hot extrusion of metals is associated with tribological failure and mechanical macrocracking. Maintaining key mechanical and tribological properties over time is the goal of developing materials and surface conditions for extrusion dies. It is worth noting that hot hardness, tempering resistance and adhesion state of coatings (e.g. CVD, PVD) are the main goals for obtaining high die life and performance.
[0005] Therefore, the object of the present invention is to propose a method for producing a die material and a die for aluminum profile extrusion, and a die having sufficient hardness, tempering resistance and adhesion properties for adhesion of a vapor deposited layer on its surface. Summary of the invention
[0006] According to a first aspect, the object of the invention is achieved by means of a method for producing a die for extrusion of an aluminium profile, the method comprising the following steps:
[0007] a) providing a first powder, which is a steel powder having the following composition in wt %:
[0008]
[0009] The balance is Fe and unavoidable / incidental impurities, the steel powder has an average particle size of 5-100 μm,
[0010] b) providing a second powder, the second powder comprising one or more grain growth inhibitors selected from carbides, oxides and nitrides,
[0011] c) grinding at least the steel powder to an average crystallite size of 20-100 nm,
[0012] d) mixing the first powder and the second powder into a powder mixture, wherein the content of the second powder in the powder mixture is in the range of 0.05-2.5 wt %,
[0013] e) forming a green body of the powder mixture,
[0014] f) sintering the green body by spark plasma sintering (SPS) at a temperature in the range of 950-1200°C.
[0015] The method may further comprise the step (g) of machining the sintered body (obtained in step f) into the shape of an extrusion die. The shaping step (g) may comprise subtractive machining.
[0016] In addition, the method may include: step (h), which includes preparing a die surface; and step (i) depositing a coating layer on the die surface. The coating layer may be a carbonitride layer, such as titanium carbonitride (Ti(C,N)). The coating layer may be deposited on the surface of the formed extrusion die by chemical vapor deposition (CVD).
[0017] The coated extrusion die may be subjected to a final heat treatment step, age hardening, to obtain the final hardness of the material.The heat treatment may be carried out at standard age hardening temperatures, such as 400-650°C, for several hours, the age hardening heat treatment being generally known to the skilled person.
[0018] According to further embodiments, the carbon content of the first powder may be below 0.8 wt %, such as below 0.5 wt %, or below 0.1 wt %.
[0019] For a particular powder and grinding equipment, the crystallite size after grinding can be measured by means of X-ray diffraction techniques. Once the grinding time required to obtain the average (i.e., mean) crystallite size is established according to the teachings of the present disclosure, the grinding time can be applied to other batches of the same powder to be ground.
[0020] By the method disclosed in the present invention, a die material for aluminum profile extrusion is provided, which has improved mechanical and tribological characteristics, particularly hardness / toughness balance and tempering tolerance compared to die materials produced according to conventional methods. Without wishing to be bound by theory, it is believed that the dispersed nanoparticles in the steel grain boundaries contribute to enhancing the thermomechanical strength and wear resistance of the steel. In addition, the microstructure of the material obtained by the present process leads to improved adhesion of the CVD-coating layer of the surface-tribological performance enhancement typically used for aluminum extrusion dies. The combination of the above material properties for aluminum extrusion dies leads to a significant improvement in the life of the tool. In addition, the microstructure of the material obtained by the process described in the present application leads to better hot strength / creep resistance, a key property of extrusion dies in the field of precision tube manufacturing for heat exchanger applications. Another advantage of using the method disclosed in the present invention is that the method allows the extrusion die material to be prepared significantly faster than the conventional method using HIP. The present process therefore allows full-density aluminum extrusion die blanks (profiles) to be obtained based on on-demand production. In addition, the method allows the blank size to be determined in preparation for machining operations, thereby eliminating the step of cutting to size, which reduces the use of equipment in die manufacturing.
[0021] SPS sintering (spark plasma sintering or discharge plasma sintering, also called pulsed current sintering) refers to a pressure sintering process based on the densification of a powder sample by applying a mechanical stress combined with the circulation of a pulsed current to heat the sample; for example, a sintering method involving hot isostatic pressing or high isostatic pressing but using the Joule effect to heat the pre-compacted powder, the assembly being subjected to a pressure of several megapascals under the action of a hydraulic press in a hollow cylindrical crucible between two graphite electrodes under an inert atmosphere or under vacuum. The pressure may be from about 1.5 MPa to about 15 MPa, but is not limited to the range stated. A direct current or an alternating current (pulsed or non-pulsed) of several thousand amperes is applied between the electrodes, and the voltage is several volts. The volts / amperes (and the applied pressure) chosen for some green bodies depends on the equipment and should therefore be adapted to the equipment. By using the SPS sintering process at a temperature below 1200°C, preferably below 1015°C, a uniform distribution of the molybdenum-rich phase and a fine and uniform microstructure are achieved, which is beneficial for further processing in the mold manufacturing process through significant but not only any high or medium temperature CVD coating process steps.
[0022] According to one embodiment, the first powder may comprise, in % by weight:
[0023]
[0024] The balance is Fe and unavoidable / incidental impurities.
[0025] The carbon content of the first powder may be less than 0.8 wt %, such as less than 0.5 wt %, or less than 0.1 wt %.
[0026] According to one embodiment, the average particle size of the first powder before grinding may be in the range of 10-50 μm. According to one embodiment, the average particle size of the first powder before grinding may be in the range of 15-25 μm. Before grinding, the first powder should have a particle size distribution that provides a good tap density, thereby providing good compaction.
[0027] According to one embodiment, after grinding, the first powder may have an average crystallite size of 20-60 nm. According to one embodiment, after grinding, the first powder may have an average crystallite size of 25-50 nm.
[0028] According to one embodiment, before grinding, the particles of the first powder may have a spherical morphology.By spherical morphology it is understood that the particles have a generally round shape, including an elliptical shape.
[0029] According to one embodiment, grinding is a type of grinding that causes the particles of the first powder to have an angular morphology. According to one embodiment, the grinding used to achieve the angular morphology may be ball milling. According to one embodiment, grinding is preferably high energy grinding (HEM). The HEM (high energy grinding or efficient grinding) method is a grinding technique for rough machining that uses a lower radial depth of cut (RDOC) and a higher axial depth of cut (ADOC). This grinding method distributes wear evenly on the cutting edge, dissipates heat, and reduces the possibility of tool failure. The grinding technique according to the present disclosure is different from traditional or conventional grinding, which typically requires a higher RDOC and a lower ADOC. In addition, while traditional grinding requires more axial passes, the HEM tool path uses more passes in the radial direction. In one embodiment, a grinding step or a pre-grinding step can be provided before the HEM grinding step. The grinding step results in a reduction in the size of the crystallites in the first powder and an increase in the number of defects in the powder due to cold welding and cracking. Through the grinding process, the sintering temperature can be significantly reduced and a finer final microstructure can be achieved in the sintered material.
[0030] In one embodiment, the grinding may be a HEM grinding-mixing step. The purpose of the HEM grinding-mixing is to obtain a homogeneous and intimate mixture of the first and second powders. It is also interesting to observe that the difference in ductility between the first and second powders makes it possible to improve the reduction of the crystallite size of the first powder while encapsulating the particles of the first powder with the particles of the second powder, which makes it possible to position the particles of the second powder at the grain boundaries of the particles of the first powder.
[0031] The combination of the HEM method and SPS sintering makes it possible to obtain sintered parts (blanks) which can be inserted into a conventional die making process chain without any modifications, since the consolidated final material blank can be fed directly to the extrusion die making process without any additional necessary steps.
[0032] Regarding the sintering step, the temperature of the green body may be raised from room temperature to the sintering temperature, preferably at 5-100°C / min, preferably at 15-75°C / min. The sintering time at the sintering temperature may be 1-45 minutes, preferably 5-30 minutes. Preferably, the method may comprise a further step of cooling the sintered material without quenching, thereby avoiding the presence of metastable phases at room temperature.
[0033] All steps of the method can be carried out in an inert atmosphere or in vacuum. The vacuum limits the risk of oxidation or nitridation of the metal.
[0034] According to one embodiment, the content of the second powder in the powder mixture may be in the range of 0.1-1.5 wt %, for example 0.25-1 wt %. According to one embodiment, the second powder contains one or more grain growth inhibitors selected from titanium carbide (TiC), tantalum carbide (TaC), tungsten carbide (WC), yttrium oxide (Y2O3), aluminum oxide (Al2O3), zirconium oxide (ZrO2), silicon nitride (Si3N4).
[0035] According to one embodiment, the second powder may contain at least 50% by weight, preferably at least 75% by weight, of yttrium oxide (Y2O3).
[0036] According to one embodiment, in the grinding step, the second powder may be ground together with the first powder. According to one embodiment, before grinding, the average particle size of the second powder may be less than 100 nm, for example less than 60 nm. Before grinding, there is no lower limit to the particle size of the second powder, however, it should be understood that the particle size of the second powder before grinding is >0.
[0037] According to one embodiment, the sintering step may include sintering at a temperature in the range of 950-1125°C, such as 960-1050°C, or 970-1000°C.
[0038] According to a second aspect, the object of the invention is also achieved by means of a die for extrusion of aluminium profiles, said die comprising a sintered body comprising dispersed intergranular nanoparticles of carbides, oxides and / or nitrides in a steel matrix having the following composition in wt. %:
[0039]
[0040] The remaining Fe and unavoidable / incidental impurities,
[0041] The carbides, oxides and / or nitrides together account for 0.05-2.5% by weight of the sintered body.
[0042] According to further embodiments, the carbon content may be below 0.8 wt. %, such as below 0.5 wt. %, or below 0.1 wt. %.
[0043] According to one embodiment, the steel matrix may comprise, in wt. %:
[0044]
[0045]
[0046] The balance is Fe and unavoidable / incidental impurities.
[0047] According to further embodiments, the carbon content may be below 0.8 wt. %, such as below 0.5 wt. %, or below 0.1 wt. %.
[0048] According to one embodiment, the grains of the steel matrix may have an angular morphology.
[0049] According to one embodiment, the content of the carbides, oxides and / or nitrides may be in the range of 0.1-1.5 wt %, such as 0.25-1 wt %.
[0050] According to one embodiment, the carbide, oxide and / or nitride may be composed of at least one of titanium carbide (TiC), tantalum carbide (TaC), tungsten carbide (WC), yttrium oxide (Y2O3), aluminum oxide (Al2O3), zirconium oxide (ZrO2), silicon nitride (Si3N4).
[0051] According to one embodiment, the carbide, oxide and / or nitride may contain at least 50% by weight, preferably at least 75% by weight, of yttrium oxide (Y2O3).
[0052] According to one embodiment, the aluminum profile extrusion die may include a carbonitride coating layer, for example, a coating layer of titanium carbonitride (Ti(C,N)), on the outer surface of the sintered body.
[0053] According to one aspect, an extrusion die is obtained by machining a blank produced by the method disclosed above into a final shape, optionally preparing the surface, and depositing a carbonitride coating, such as a coating of titanium carbonitride (Ti(C,N)), on the final shaped die surface.
[0054] According to a third aspect, the present disclosure relates to a method for preparing an extrusion die blank material, the method comprising the steps of:
[0055] a) providing a first powder, which is a steel powder having the following composition in wt %:
[0056]
[0057] The balance is Fe and unavoidable / incidental impurities, the steel powder has an average particle size of 5-100 μm,
[0058] b) providing a second powder, the second powder comprising one or more grain growth inhibitors selected from carbides, oxides and nitrides,
[0059] c) grinding at least the steel powder to an average crystallite size of 20-100 nm,
[0060] d) mixing the first powder and the second powder into a powder mixture, wherein the content of the second powder in the powder mixture is in the range of 0.05-2.5 wt %,
[0061] e) forming a green body of the powder mixture,
[0062] f) sintering the green body by spark plasma sintering (SPS) at a temperature in the range of 950-1200°C.
[0063] According to one embodiment, the first powder may comprise, in % by weight:
[0064]
[0065] The balance of Fe and occasional impurities.
[0066] The carbon content of the first powder may be less than 0.8 wt %, such as less than 0.5 wt %, or less than 0.1 wt %.
[0067] According to one embodiment, the average particle size of the first powder before grinding may be in the range of 10-50 μm; or in the range of 15-25 μm.
[0068] According to one embodiment, after grinding, the average crystallite size of the first powder may be in the range of 20-60 nm; or in the range of 25-50 nm.
[0069] According to one embodiment, the particles of the first powder may have a spherical or rounded morphology prior to grinding.
[0070] According to one embodiment, the grinding may be of a type that results in particles of the first powder having an angular morphology.
[0071] According to one embodiment, the content of the second powder in the powder mixture may be in the range of 0.1-1.5 wt %; or in the range of 0.25-1 wt %; or in the range of 0.25-1 wt %.
[0072] According to one embodiment, the second powder may contain one or more grain growth inhibitors selected from titanium carbide (TiC), tantalum carbide (TaC), tungsten carbide (WC), yttrium oxide (Y2O3), aluminum oxide (Al2O3), zirconium oxide (ZrO2), and silicon nitride (Si3N4).
[0073] According to one embodiment, the second powder may contain at least 50% by weight, preferably at least 75% by weight, of yttrium oxide (Y2O3).
[0074] According to one embodiment, the second powder may be ground together with the first powder in the grinding step.
[0075] According to one embodiment, the sintering step may include sintering at a temperature in the range of 950-1125°C, or 960-1050°C, or 970-1000°C.
[0076] The features and characteristics of the method according to the third aspect are the same as the corresponding steps and features described for the method according to the first aspect. Therefore, the same advantages and technical effects are obtained for the same method steps.
[0077] According to a fourth aspect, the objects of the invention are also achieved by an extrusion die blank material comprising a sintered body comprising dispersed intergranular nanoparticles of carbides, oxides and / or nitrides in a steel matrix, the steel matrix having the following composition in wt. %:
[0078]
[0079] The remaining Fe and unavoidable / incidental impurities,
[0080] The carbides, oxides and / or nitrides together account for 0.05-2.5% by weight of the sintered body.
[0081] According to one embodiment, the steel matrix may comprise, in wt. %:
[0082]
[0083] The balance of Fe and occasional impurities.
[0084] According to further embodiments, the carbon content may be below 0.8 wt. %, such as below 0.5 wt. %, or below 0.1 wt. %.
[0085] According to one embodiment, the grains of the steel matrix may have an angular morphology.
[0086] According to one embodiment, the content of the carbides, oxides and / or nitrides may be in the range of 0.1-1.5 wt %, such as 0.25-1 wt %.
[0087] According to one embodiment, the carbide, oxide and / or nitride may be composed of at least one of titanium carbide (TiC), tantalum carbide (TaC), tungsten carbide (WC), yttrium oxide (Y2O3), aluminum oxide (Al2O3), zirconium oxide (ZrO2), silicon nitride (Si3N4).
[0088] According to one embodiment, the carbide, oxide and / or nitride may contain at least 50% by weight, preferably at least 75% by weight, of yttrium oxide (Y2O3).
[0089] The term "blank" or "die blank" should be understood to mean a workpiece that can be further processed or machined to obtain the final shaped extrusion die. BRIEF DESCRIPTION OF THE DRAWINGS
[0090] Figure 1 The bar graph shows the approximate life of the extrusion die at an operating temperature of 600°C. Figure 3 Comparison of steel hardness, Vickers hardness, drop (HV hardness change on the y-axis) between a prior art embodiment (left pair of bars) and an embodiment of the present invention (right pair of bars) produced by the process shown.
[0091] Figure 2 The steps of a method for manufacturing a part or an article including a HEM grinding process and an SPS sintering process according to one embodiment of the present disclosure are shown.
[0092] Figure 3 The steps of a method for manufacturing a part or a product according to the prior art are shown, which include a high isostatic pressing (HIP) step, a hot rolling step, and a cutting-to-length step. DETAILED DESCRIPTION
[0093] In the following, exemplary embodiments of the present invention will be discussed in more detail. It should be understood, however, that the exemplary embodiments are not intended to limit the present invention, since the scope of the present invention is defined by the appended claims.
[0094] The study was conducted by evaluating the mechanical properties of steel samples sintered by SPS from mechanically activated steel powders. The process for producing dense nanostructured samples from micron-sized commercial powders consists of two steps:
[0095] (i) mechanical activation of the elemental powder by grinding,
[0096] (ii) The powder is densified in one step by flash sintering using an SPS apparatus.
[0097] The conditions for powder preparation were chosen to produce the formulation required to perform SPS samples.
[0098] The powders were ground in a planetary ball vario-mill with specific ball milling conditions and established between 0 and 4000 rpm (revolutions per minute), ie with respect to absolute rotational speed a disc rotational speed between 0 and + / - 4000 rpm.
[0099] Additionally, the grinding parameters were selected so that grinding lasted from 4 to 8 hours for producing a mechanically activated mass.
[0100] According to one example, a steel powder is provided which consists, in weight % (wt %), of:
[0101]
[0102] Furthermore, a second powder is added which consists in weight % (wt. %) of between 0.05 and 2.5% of the total content of the powder.
[0103] The powder comprising the steel powder and the second powder was then ground in open air using a HEM process to obtain steel particles having a crystallite size of less than 60 nanometers. The following grinding parameters were used: grinding disk speed: 250 rpm, for 4 hours, in open air, drying process, the mass ratio of powder to ball weight was between 1 / 5 and 1 / 9.
[0104] The powder is then sintered at a temperature below 1050°C using an SPS sintering process. By observing the mold / sample, it was found that the SPS sintering process temperature should preferably be below 1015°C. The temperature is measured directly on the final part or on the tool holder of the part. The SPS sintering parameters are: uniaxial stress 50MPa, dwell time 30 minutes, and cooling without quenching.
[0105] refer to Figure 1 The right side of the method according to the prior art (reference Figure 3 ) in the material produced according to the previous embodiment example, the steel hardness drop is reduced. The same sample was baked at 600°C and then taken out every 24 hours and then allowed to cool to room temperature for hardness measurement. The hardness measurement was performed every 24 hours and shows the evolution of hardness with heat aging.
[0106] Figure 2 An example of an extrusion die manufacturing method according to the present disclosure is shown, comprising the following steps:
[0107] - alloying (melt),
[0108] - atomization of powders including steel powder,
[0109] -HEM grinding,
[0110] -SPS sintering,
[0111] - Mould making,
[0112] - surface preparation,
[0113] -CVD step,
[0114] - a heat treatment step,
[0115] Thus, an extrusion die based on ODS (oxide dispersion strengthened) steel is obtained.
[0116] Compared with the prior art (see Figure 3 ), the combination of the steps HEM grinding and SPS sintering makes it possible to obtain aluminum-based steel dies for extruding aluminum profiles, which present improved mechanical and tribological characteristics, in particular hardness / toughness balance, excellent adhesion of CVD layers such as titanium carbonitride (Ti(C,N)) layers to the substrate (die surface), directly leading to an increase in the extrusion die life. In addition, dislocation propagation, creep and deformation of the extrusion die are reduced. In addition to the above characteristics, the microstructure of the material obtained by the process described in the present disclosure leads to better hot strength / creep resistance, which is a key property of extrusion dies in the field of precision tube manufacturing for heat exchanger applications.
Claims
1. A method for producing a die for extrusion of an aluminum profile, the method comprising the following steps: a) providing a first powder, which is a steel powder having the following composition in wt %: C<1.2 Co 6.0-15 Mo 5.0-11.0 Mn 0-1.5 Si 0-1.25 Cr 2-8 Ni 0.5-6.0 P<0.1 The balance is Fe and inevitable impurities, the steel powder has an average particle size of 5-100 μm, b) providing a second powder, the second powder comprising one or more grain growth inhibitors selected from carbides, oxides and nitrides, c) grinding at least the steel powder to an average crystallite size of 20-100 nm, d) mixing the first powder and the second powder into a powder mixture, wherein the content of the second powder in the powder mixture is in the range of 0.05-2.5 wt %, e) forming a green body of the powder mixture, f) sintering the green body by spark plasma sintering (SPS) at a temperature in the range of 950-1200°C.
2. The method according to claim 1, wherein: In weight %, the first powder comprises: C<1.2 Co 8.0-9.0 Mo 6.0-8.0 Mn 0.1-0.5 Si 0.05-0.20 Cr 3-5 Ni 1.0-3.0 P<0.1 The balance is Fe and inevitable impurities.
3. The method according to claim 1 or 2, wherein the average particle size of the first powder before grinding is in the range of 10-50 μm.
4. The method according to claim 1 or 2, wherein the average particle size of the first powder before grinding is in the range of 15-25 μm.
5. A method according to any preceding claim, wherein: After grinding, the first powder had an average crystallite size of 20-60 nm.
6. A method according to any preceding claim, wherein: Before grinding, the particles of the first powder have a spherical morphology.
7. A method according to any preceding claim, wherein the grinding is of a type that results in particles of the first powder having an angular morphology.
8. A method according to any preceding claim, wherein the content of the second powder in the powder mixture is in the range of 0.1-1.5 wt%.
9. A method according to any preceding claim, wherein the content of the second powder in the powder mixture is in the range of 0.25-1 wt%.
10. A method according to any preceding claim, wherein the second powder contains one or more grain growth inhibitors selected from titanium carbide (TiC), tantalum carbide (TaC), tungsten carbide (WC), yttrium oxide (Y2O3), aluminum oxide (Al2O3), zirconium oxide (ZrO2), silicon nitride (Si3N4).
11. A method according to any preceding claim, wherein the second powder comprises at least 50 wt%, or at least 75 wt%, yttrium oxide (Y2O3).
12. A method according to any preceding claim, wherein in the grinding step the second powder is ground together with the first powder.
13. The method of any preceding claim, wherein the sintering step comprises sintering at a temperature in the range of 950-1125°C, 960-1050°C, or 970-1000°C.
14. A method according to any preceding claim, wherein the method further comprises the steps of (g) machining the sintered body obtained in (f) into a final mould shape and depositing a titanium carbonitride layer on the surface of the sintered body by means of chemical vapour deposition (CVD).
15. A die for extrusion of aluminum profiles, the die comprising a sintered body comprising intergranular nanoparticles of carbides, oxides and / or nitrides located between steel grains in a steel matrix, the steel matrix having the following composition in weight %: C<1.2 Co 6.0-15 Mo 5.0-11.0 Mn 0-1.5 Si 0-1.25 Cr 2-8 Ni 0.5-6.0 P<0.1 The balance of Fe and unavoidable impurities, The carbides, oxides and / or nitrides together account for 0.05-2.5% by weight of the sintered body.
16. The mold of claim 15, wherein the carbon content of the steel matrix is less than 0.8 wt%, less than 0.5 wt%, or less than 0.1 wt%.
17. The mold according to any one of claims 15 or 16, wherein the steel matrix comprises, in weight %: C<1.2 Co 8.0-9.0 Mo 6.0-8.0 Mn 0.1-0.5 Si 0.05-0.20 Cr 3-5 Ni 1.0-3.0 P<0.1 The balance is Fe and inevitable impurities.
18. The mold according to any one of claims 15 to 17, wherein the grains of the steel matrix have an angular morphology.
19. The mold according to any one of claims 15 to 18, wherein the content of the carbide, oxide and / or nitride is in the range of 0.1-1.5 wt%, or 0.25-1 wt%.
20. The mold according to any one of claims 15-19, wherein the carbide, oxide and / or nitride is composed of at least one of titanium carbide (TiC), tantalum carbide (TaC), tungsten carbide (WC), yttrium oxide (Y2O3), aluminum oxide (Al2O3), zirconium oxide (ZrO2), and silicon nitride (Si3N4).
21. The mold according to any one of claims 15 to 20, wherein the carbide, oxide and / or nitride comprises at least 50 wt%, or at least 75 wt%, of yttrium oxide (Y2O3).
22. The mold according to any one of claims 15 to 21, wherein the mold comprises a titanium carbonitride (Ti(C,N)) layer on an outer surface of the sintered body.
23. A method for preparing a blank material for an extrusion die, the method comprising the steps of: a) providing a first powder, which is a steel powder having the following composition in wt %: C<1.2 Co 6.0-15 Mo 5.0-11.0 Mn 0-1.5 Si 0-1.25 Cr 2-8 Ni 0.5-6.0 P<0.1 The balance is Fe and occasional impurities, the steel powder has an average particle size of 5-100 μm, b) providing a second powder, the second powder comprising one or more grain growth inhibitors selected from carbides, oxides and nitrides, c) grinding at least the steel powder to an average crystallite size of 20-100 nm, d) mixing the first powder and the second powder into a powder mixture, wherein the content of the second powder in the powder mixture is in the range of 0.05-2.5 wt %, e) forming a green body of the powder mixture, f) sintering the green body by spark plasma sintering (SPS) at a temperature in the range of 950-1200°C.
24. The method of claim 23, wherein the first powder comprises, in weight %,: C<1.2 Co 8.0-9.0 Mo 6.0-8.0 Mn 0.1-0.5 Si 0.05-0.20 Cr 3-5 Ni 1.0-3.0 P<0.1 The balance of Fe and occasional impurities.
25. The method of claim 23 or 24, wherein the carbon content of the first powder is less than 0.8 wt%, or less than 0.5 wt%, or less than 0.1 wt%.
26. The method of any one of claims 23-25, wherein the average particle size of the first powder before grinding is in the range of 10-50 μm; or in the range of 15-25 μm.
27. The method of any one of claims 23-26, wherein after grinding, the first powder has an average crystallite size of 20-60 nm.
28. The method according to any one of claims 23 to 27, wherein: Before grinding, the particles of the first powder have a spherical or rounded morphology.
29. The method of any one of claims 23-28, wherein the grinding is of a type that results in particles of the first powder having an angular morphology.
30. The method according to any one of claims 23 to 29, wherein the content of the second powder in the powder mixture is in the range of 0.1 to 1.5 wt. %, or in the range of 0.25 to 1 wt. %.
31. The method according to any one of claims 23 to 30, wherein the second powder contains one or more grain growth inhibitors, and the one or more grain growth inhibitors are selected from titanium carbide (TiC), tantalum carbide (TaC), tungsten carbide (WC), yttrium oxide (Y2O3), aluminum oxide (Al2O3), zirconium oxide (ZrO2), and silicon nitride (Si3N4).
32. The method of any one of claims 23-31, wherein the second powder comprises at least 50 wt%, or at least 75 wt%, yttrium oxide (Y2O3).
33. The method according to any one of claims 23 to 32, wherein in the grinding step the second powder is ground together with the first powder.
34. The method of any one of claims 23-33, wherein the sintering step comprises sintering at a temperature in the range of 950-1125°C, or 960-1050°C, or 970-1000°C.
35. An extrusion die blank material comprising a sintered body comprising dispersed intergranular nanoparticles of carbides, oxides and / or nitrides in a steel matrix having the following composition in weight %: C<1.2 Co 6.0-15 Mo 5.0-11.0 Mn 0-1.5 Si 0-1.25 Cr 2-8 Ni 0.5-6.0 P<0.1 The remaining Fe and occasional impurities, The carbides, oxides and / or nitrides together account for 0.05-2.5% by weight of the sintered body.
36. The extrusion die blank material according to claim 35, wherein: In weight %, the steel matrix comprises: C<1.2 Co 8.0-9.0 Mo 6.0-8.0 Mn 0.1-0.5 Si 0.05-0.20 Cr 3-5 Ni 1.0-3.0 P<0.1 The balance of Fe and occasional impurities.
37. The extrusion die blank material according to any one of claims 35-36, wherein the carbon content is less than 0.8 wt%, or less than 0.5 wt%, or less than 0.1 wt%.
38. The extrusion die blank material according to any one of claims 35 to 37, wherein the grains of the steel matrix have an angular morphology.
39. An extrusion die blank material according to any one of claims 36 to 38, wherein the content of carbides, oxides and / or nitrides is in the range of 0.1-1.5 wt%, such as 0.25-1 wt%.
40. The extrusion die blank material according to any one of claims 35-39, wherein the carbide, oxide and / or nitride is composed of at least one of titanium carbide (TiC), tantalum carbide (TaC), tungsten carbide (WC), yttrium oxide (Y2O3), aluminum oxide (Al2O3), zirconium oxide (ZrO2), and silicon nitride (Si3N4).
41. The extrusion die blank material of any one of claims 35-40, wherein the carbide, oxide and / or nitride comprises at least 50 wt%, or at least 75 wt%, yttrium oxide (Y2O3).